The rubber industry of Thailand: A review of past achievements and future prospects - Pornthep Weerathamrongsak (2018)
Purpose - The purpose of this paper is to provide an overview of the recent developments in the natural rubber industry and identify the major factors that will likely determine the sustainability of Thailand’s competitive advantage in this area. Design/methodology/approach - Data were gathered through in depth interviews with industry experts both in the private and public sectors. The obtained information was then analyzed under the standard framework of national competitiveness widely referred to as the Diamond Model. Findings - The recent success of the Thai rubber industry stems from the competitiveness of local firms in the upstream industry and the leadership of foreign firms in the downstream sector. To further strengthen competitiveness, a more concerted effort to encourage innovation and technology absorption by local downstream firms is required. Originality/value - This research provides a comprehensive overview of one of Thailand’s most significant agricultural exporting industries. It systematically analyzes the sector’s strengths and weaknesses and offers recommendations for policy makers to manage future opportunities and threats. © Emerald Group Publishing Limited.